Scientific Literacy Test Instrument for Junior High School in Pati: The Validity and Reliability - Isrofi'atun; Rusilowati, Ani; Supriyadi (Universitas Negeri Semarang, 2024)
This research uses a modified Research and Development (R&D) research and development model from Thiagarajan's Four D, namely defining, designing, developing, and disseminating. The product of this research is a science literacy test instrument for junior high school science subjects in Pati Regency. Expert assessment by 4 assessors, including; 1 lecturer, 1 language expert, and 2 junior high school science teachers. The testing carried out by experts is instrument evaluation, the results of testing the validity and reliability of the scientific literacy test instrument for junior high school students. The test instrument developed obtained language percentage results of 86%, very good, 87% very good in construction, and 89% good in material. The expert validity assessment in developing scientific literacy test instruments produced a v'Aikens index test result of 0.8120, which is included in the high validity criterion. The results of the reliability test show an average size of 0.684 which is included in the ICC criteria for good reliability. development of scientific literacy test instruments as a whole is valid and can be used as a reference by teachers.